2010
DOI: 10.1073/pnas.1008843107
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus anthracis produces membrane-derived vesicles containing biologically active toxins

Abstract: Extracellular vesicle production is a ubiquitous process in Gram-negative bacteria, but little is known about such process in Gram-positive bacteria. We report the isolation of extracellular vesicles from the supernatants of Bacillus anthracis, a Gram-positive bacillus that is a powerful agent for biological warfare. B. anthracis vesicles formed at the outer layer of the bacterial cell had double-membrane spheres and ranged from 50 to 150 nm in diameter. Immunoel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
345
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(368 citation statements)
references
References 46 publications
14
345
1
1
Order By: Relevance
“…Bacillus anthracis is among the few Grampositive bacteria, which produces membrane vesicles. Membrane vesicles derived from Bacillus anthracis is reported to contain the anthrolysin O apart from lethal toxin/edema toxin, indicating the physiological role of anthrolysin O during anthrax infections [62]. Bishop and colleague have studied the effect of recombinant purified anthrolysin O on the integrity of gut epithelial barrier in human C2BBE and ex vivo mouse intestinal segments.…”
Section: Anthrolysin Omentioning
confidence: 99%
“…Bacillus anthracis is among the few Grampositive bacteria, which produces membrane vesicles. Membrane vesicles derived from Bacillus anthracis is reported to contain the anthrolysin O apart from lethal toxin/edema toxin, indicating the physiological role of anthrolysin O during anthrax infections [62]. Bishop and colleague have studied the effect of recombinant purified anthrolysin O on the integrity of gut epithelial barrier in human C2BBE and ex vivo mouse intestinal segments.…”
Section: Anthrolysin Omentioning
confidence: 99%
“…EMVs produced by these bacteria are derived from the cytoplasmic membrane and are 20-250 nm in diameter (Lee et al 2009;Schrempf et al 2011). It has been suggested that the vesicles produced by monoderm bacteria are like their diderm counterparts, involved in pathogenesis (Rivera et al 2010;Prados-Rosales et al 2011). Enzymes involved in peptidoglycan degradation, antibiotic degradation, virulence factors (anthrolysin, anthrax toxin components, coagulases, hemolysins and lipases) and immunologically-active compounds have been identified in these vesicles (Marsollier et al 2007;Lee et al 2009;Rivera et al 2010;Gurung et al 2011;Prados-Rosales et al 2011;Thay et al 2013;Brown et al 2014).…”
Section: Emvs In Bacteriamentioning
confidence: 99%
“…They are naturally produced by both pathogenic and nonpathogenic Gram negative bacteria like -Neisseria, Helicobacter pylori, Vibrio cholerae, Haemophilus influenzae (Schooling et al, 2006). However Gram positive bacteria like Bacillus anthracis (Rivera et al, 2010) and Mycobacteria spp (Prados-Rosales et al, 2011) have also been reported to produce outer membrane vesicles. OMV allows bacteria to secrete insoluble and complex molecules with the soluble material so that it reach the target in a concentrated and protected form and helps in bacterial stress response, nutrient acquisition, biofilm development (Mashburn-Warren et al, 2006).…”
Section: Introductionmentioning
confidence: 99%